Perbaikan Postur Kerja Operator Cast House dengan Metode REBA di PT XYZ - Tri Joko Wibowo; Ikko Novan (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2020)
Musculoskeletal disorders (MSDs) are diseases in the human muscular tissue system in the back, wrist, knees and shoulders caused by incorrect postur during work activities. This study was conducted to determine the level of risk MSDs on operator work activities at the cast house work station. Activities under study are activities; surface repair tap hole, checking temperature iron, and take iron sample. These activities are carried out repeatedly, incorrect work posture and the presence of heat from work environment factors that affect the whole body. This makes the operator complain of pain in parts of the body at risk of developing musculoskeletal complaints. This study was an observational study using the Rapid Entire Body Assessment method and the Nordic Body Map instrumen. The result of the Nordic Body Map instrumen for 20 operators at the cast house work station showed that there were 21 complaints against operator. Based on the measurement of cast house operators the surface repair activity of tap holes has a “high” risk value for MSDs (REBA Score 9), checking temperature iron activities have a “low” risk value for MSDs. Proposed improvement to prevent is to improve the procedur in the surface repair activities of tap holes, where when the process of sticking the dough is done in front of the tap hole is changed by attaching it to the mud gun nozzle tip. After the proposed improvement, the result of the Nordic Body Map instrumen showed no complaints and the measurement of the tap hole had a “low” risk value for the occurrence of MSDs (REBA Score 3).